Halloween party murder [large type] - Ross, Barbara, 1953- (Thorndike Press large print mystery, 2021)
"Tinker's Cove newest residents Ty and Heather Moon turn their Victorian home into a haunted house to raise funds for charity. But the Halloween fun turns to horrific fright when Heather overdoses on tainted drugs--and Ty finds himself accused of murder. Digging deep into the story, journalist Lucy Stone uncovers some sinister secrets in the Moons' past linked to a conspiracy in her hometown... DEATH OF A HALLOWEEN PARTY MONSTER by LEE HOLLIS Everyone attending Island Times Food and Cocktail columnist Hayley Powell's Halloween bash is dressed as their favorite movie monster from the Bride of Frankenstein and Jaws to Chucky and Pennywise the clown. But when partygoers stumble upon Boris Candy's bludgeoned costumed corpse, it falls to Hayley to discover who among her guests wanted to stop the man from clowning around permanently... SCARED OFF by BARBARA ROSS Three teenage girls having a sleepover on Halloween night get spooked when high schoolers crash the house for a party. But no one expected to find a crasher like Mrs. Zelisko, the elderly third floor tenant, dead in the backyard--dressed in a sheet like a ghost. With her niece traumatized, Julia Snowden must uncover who among the uninvited guests was responsible for devising such a murderous trick.."--Provided by publisher.